Discovery: insurance that bridges the gap between intent and action - Kolster, Thomas (Henry Stewart Talks, 2021)
This case study looks at Discovery’s Vitality programme as a successful example of a company bridging the gap between intent and action, helping their business by incentivizing their customers to make healthy choices.